Docking, scoring, and affinity prediction in CAPRI. Issue 12 (17th October 2013) - Lensink, Marc F.; Wodak, Shoshana J.; Bonvin, Alexandre M. J. J.; Janin, Joël; Wodak, Shoshana J.
ABSTRACT We present the fifth evaluation of docking and related scoring methods used in the community‐wide experiment on the Critical Assessment of Predicted Interactions (CAPRI). The evaluation examined predictions submitted for a total of 15 targets in eight CAPRI rounds held during the years 2010–2012. The targets represented one the most diverse set tackled by the CAPRI community so far. They included only 10 "classical" docking and scoring problems. In one of the classical targets, the new challenge was to predict the position of water molecules in the protein–protein interface. The remaining five targets represented other new challenges that involved estimating the relative binding affinity and the effect of point mutations on the stability of designed and natural protein–protein complexes. Although the 10 classical CAPRI targets included two difficult multicomponent systems, and a protein–oligosaccharide complex with which CAPRI participants had little experience, this evaluation indicates that the performance of docking and scoring methods has remained quite robust. More remarkably, we find that automatic docking servers exhibit a significantly improved performance, with some servers now performing on par with predictions done by humans. The performance of CAPRI participants in the new challenges, briefly reviewed here, was mediocre overall, but some groups did relatively well and their approaches suggested ways of improving methods for designing binders and for estimating the free energies of protein assemblies, which should impact the field of protein modeling and design as a whole. Proteins 2013; 81:2082–2095. © 2013 Wiley Periodicals, Inc.